Reconocimiento e identificacion de enemigos naturales de moscas blancas (Homoptera: Aleyrodidae) en Colombia y Ecuador - Lopez Avila, O.=700 1 Cardona Mejia, C.; Garcia Gonzalez, J.; Rendon, F.; Hernandez, P.
(Es, En)
Ilus., 7 ref.
Keywords: INSECTA; HOMOPTERA; ALEYRODIDAE; ESPECIES; DEPREDADORES; PARASITOIDES; HONGOS ENTOMOPATOGENOS; ENEMIGOS NATURALES; DISTRIBUCION GEOGRAFICA; COLOMBIA; ECUADOR; MOSCAS BLANCAS